1977
DOI: 10.1085/jgp.70.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain-insensitive salt and water movements in duck red cells. I. Kinetics of cation transport under hypertonic conditions.

Abstract: Duck red cells in hypertonic media experience rapid osmotic shrinkage followed by gradual reswelling back toward their original volume. This uptake of salt and water is self limiting and demands a specific ionic composition of the external solution. Although ouabain (10(-4)M) alters the pattern of cation accumulation from predominantly potassium to sodium, it does not affect the rate of the reaction, or the total amount of salt or water taken up. To study the response without the complications of active Na-K t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

1977
1977
1989
1989

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(57 citation statements)
references
References 25 publications
2
54
1
Order By: Relevance
“…We have shown that cells incubated with ouabain in the absence of norepinephrine or hypertonicity maintain relatively stable volume by a simple exchange of internal potassium for incoming sodium (Schmidt and McManus, 1977a). The addition of furosemide to catecholamine-stimulated or hypertonically activated cells resuits in a stabilization of cell volume by a similar mechanism (Schmidt and McManus, 1977a, b).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We have shown that cells incubated with ouabain in the absence of norepinephrine or hypertonicity maintain relatively stable volume by a simple exchange of internal potassium for incoming sodium (Schmidt and McManus, 1977a). The addition of furosemide to catecholamine-stimulated or hypertonically activated cells resuits in a stabilization of cell volume by a similar mechanism (Schmidt and McManus, 1977a, b).…”
Section: Discussionmentioning
confidence: 97%
“…When ceils were added to hypertonic solutions, the initial samples were taken as rapidly as possible (see Schmidt and McManus, 1977a). Both hypertonic and isotonic incubation solutions always contained (mM): ouabain, 0.1; glucose, 10; inorganic phosphate, 2.0-5.0; magnesium, 1.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was marked variation in tissue Na concentrations between different animal groups, ranging from 44 (Table la) to 102 (Table Ic) + For experiments with pericellular osmolality from 299 to 385 mosmol/kg IW (constant Na, n = 88). (Schmidt and McManus, 1977) and underscores the necessity for paired experiments. Similar variation between batches of tissue slices for Cl can be noted but less so for K. These control values lie well within the reported ranges for kidney tissue of rat or rabbit (Hughes and MacKnight, 1976;Law, 1975;Povedin and Boumedil-Povedin, 1972) and are amongst the lowest for Na and the highest for K reported even at 25°, indicating that there was no difficulty in maintaining oxygenation of these slices at 37°.…”
Section: Resultsmentioning
confidence: 98%
“…This tendency to restore original cell volume is referred to as volume regulation and is incomplete in renal epithelial cells but nearly complete in red cells (Kregenow, 1971a;Schmidt and McManus, 1977). The mechanism for this partial return to original cell volume in kidney cells has been variously attributed to a cation pump, either sensitive to inhibition of the Na"*"-, K+-ATPase by cardiac glycosides (Whittam and Willis, 1963) or not (Kleinzeller and Knotkova, 1964;Hughes and MacKnight, 1976), in which case a second cardiac glycoside-insensitive pump has been postulated (Schmidt and McManus, 1977). It has also been attributed to physical elastic 'recoil' forces of the cell (Kleinzeller and Knotkova, 1964) or its basement membrane (Linshav/ et al, 1977).…”
Section: Introductionmentioning
confidence: 99%